Cover Feature: Potential‐Modulated Ion Distributions in the Back‐to‐Back Electrical Double Layers at a Polarised Liquid|Liquid Interface Regulate the Kinetics of Interfacial Electron Transfer (ChemElectroChem 3/2023). Issue 3 (23rd January 2023) - Gamero‐Quijano, Alonso; Manzanares, José A.; Ghazvini, Seyed M. B. H.; Low, Paul J.; Scanlon, Micheál D.
Abstract : The Cover Feature illustrates that saturation of the organic electrolyte anion (orange balls) in the electric double layer on the organic side of a positively polarized liquid|liquid interface is compensated by an accumulation of protons (blue balls) on the aqueous side. The latter enhances the kinetics of interfacial electron transfer between protons and organic soluble decamethylferrocene in the presence of O2, yielding H2 O2 (image design by Dr Shayon Bhattacharya, University of Limerick). More information can be found in the Research Article by A. Gamero‐Quijano, M. D. Scanlon and co‐workers .